'Prisons and the Public' by Margaret Bondfield, JP. (11th October 2021) - SPARKS, RICHARD
Abstract: This short article revisits the address that Margaret Bondfield gave to the Howard League for Penal Reform's inaugural annual general meeting, a little over 100 years ago. It seeks both to illuminate the framing of her argument, and note some features of the moment and situation to which it was addressed. I argue that while it is true that Bondfield's speech reveals certain tensions that have remained somewhat intractable in the field of penal reform ever since, it also demonstrates a conviction and ambition that contemporary actors might well wish to seek to recover.